Preservação de amostras de folhas do mamoeiro para detecção dos vírus da meleira (PMeV E PMeV2) por diagnóstico molecular - Santana, Ana Paula de Jesus (2024)
The papaya blight disease is caused by the papaya blight virus complex (PMeV and PMeV2). The strategy for controlling the disease is to identify symptomatic plants that are removed from the field using the roguing technique. However, there is often a need for molecular confirmation of plants suspected of being infected. Improving techniques for maintaining the virus in biological material, such as herborization, can help in time scale studies of viral genomics. The aim of this study was to evaluate a methodology for collecting, preserving and storing samples of papaya leaves infected by the blight virus complex for molecular diagnosis. The efficiency of herborization and storage in preserving papaya leaf samples for diagnosis was determined. The samples were collected manually by cutting young leaves, preferably with apical lesions characteristic of the symptoms of blight. A total of 48 samples were separated into two differently stored groups, 24 kept in an ultrafreezer and 24 herbarized, which in turn were subdivided into two subgroups with 12 asymptomatic samples (UM and HM) and 12 symptomatic samples (UA and HA). Analyses for the molecular diagnosis of the PMeV and PMeV2 viruses were carried out at intervals of zero (T0), five (T5), ten (T10), twenty (T20) and forty (T40) days after storage. It was observed that at T20 and T40 all the samples showed the presence of the PMeV viral complex in both forms of preservation. However, the analyses at times T5 and T10 did not obtain a uniform pattern for identifying the virus, possibly due to the non-uniform distribution of the viruses in the cells of the papaya leaves. The results validated an alternative methodology for recommending a new low-cost and easy-to-use sample preservation and storage protocol for the molecular diagnosis of papaya blight